The Effect of E-Servicescape on Customer Satisfaction through E-Service Quality: Evidence from Shopee Marketplace Users - Mahotama Putera, Anak Agung Gde Raditya; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to examine the influence of e-servicescape on customer satisfaction and investigate the mediating role of e-service quality in the context of the Shopee marketplace. Design/methodology/approach – This study employs a quantitative research design using an associative approach to examine the relationships among the proposed variables. The population consists of Shopee marketplace users in Malang City. Using a purposive sampling technique, data were collected from 150 respondents through Likert-scale questionnaires measuring their attitudes and perceptions. The proposed model was analyzed using Structural Equation Modeling (SEM) with SmartPLS 4.0. Findings – The results reveal that e-servicescape has a positive and significant effect on customer satisfaction and e-service quality. Furthermore, e-service quality positively and significantly influences customer satisfaction and serves as a mediating variable in the relationship between e-servicescape and customer satisfaction. These findings indicate that an effective digital service environment enhances perceived service quality, which in turn improves customer satisfaction. Originality/value – This study extends the understanding of the e-servicescape concept by integrating it with e-service quality as a mediating factor in the context of online marketplaces. The findings provide valuable implications for e-commerce platforms in improving customer experience through optimized digital design and service quality.